Islamic Religious Education and Local Wisdom in Shaping the Religious Behavior of Industrialized Communities in Gresik, Indonesia) - Mohammad Ahyan Yusuf Sya'bani (Budapest International Research and Critics University, 2022)
The religious behavior of industrialized communities in Gresik in the context of Islamic religious education and local wisdom is strongly influenced by the geographical location of the city of Gresik as a coastal area north of Java that seems to live with extreme circumstances. In addition, the socio-cultural background is also an interesting factor that is even more influential on the religious behavior of gresik people based on industry. In the long run, Gresik was known as the mayor's city and then the city of Santri. But now the icon has changed that Gresik as an industrial city as many factories, companies, and other modern buildings are established. Then came the industrial society in Gresik which was born from various social elements of society both religious, traditionalist, modernist, liberal, nationalist, and many more.